تقدير ومقارنة السمية الحادة لبعض العناصر الثقيلة تجاه نوعين من قواقع المياه العذبة - القاروني عماد هادي محسن (University of Thi-Qar Journal of Science, 2014)
LC50 for heavy metals Cadmium, Lead, Cobalt, Nickel, Silver and Mercury to two snails species Lymnaea auricularia and Physa acuta had been Estimated during 96 h. LC50 was high for Lead 9.667 ppm for Physa acuta and low for Mercury 0.281 ppm for Lymnaea auricularia. significant correlations for LC50 had been found between Lymnaea auricularia and Physa acuta . heavy metals toxicity followed this order Pb < Cd< Ni< Co< Ag <Hg. Mortality percentage did not occur for strontium on study snails with concentration from 1 until 30 ppm.